Pengaruh Persepsi Tentang Tugas dan Motivasi Kerja Terhadap Kinerja Guru Bimbingan Dan Konseling - Wens Nagul; Stefanus Lio; Matilda Pia Bone; Rosa M Bulor (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study aimed to determine the effect of perceptions about assignments and work motivation on the performance of Guidance and Counseling teachers. This research was conducted on all Guidance and Counseling teachers who served in Junior High Schools and Senior High Schools who became the Guidance and Counseling apprenticeship partner schools of the Guidance and Counseling Department at Education Faculty of Catholic University of Widya Mandira Kupaang, totaling 30 people. The instrument used in this study was a questionnaire using a Likert scale model with correlation and regression data analysis. The results of the study showed that there was a significant influence of the perception variable about assignments on the performance of the Guidance and Counseling teachers, there was a significant influence of the work motivation variable on the performance of the Guidance and Counseling teachers, and there was a significant influence of the perception of the task and work motivation on the performance of the Guidance and Counseling teachers.